Mathematical Model of Vacuum Evaporation Using Apparatus with Mechanical Water Vapor Recompression - A. Shirkin, L.; G. Selivanov, O.; A. Trifonova, T.; I. Roshchina, S.; E. Ilina, M. (International Journal of Engineering and Technology, 2018)
This article presents mathematical model of evaporation of aqueous solutions of mineral salts on apparatus with mechanical recompression of water vapor and process intensification upon vacuuming. The developed mathematical model is an engineering prediction where all calculations are associated with technological flowchart of evaporator. Predictions according to the mathematical model for evaporator are exemplified for the case of 2% aqueous solution of sodium chloride evaporated to 15 wt % at distillation capacity of 30 kg/h. Engineering predictions were performed consecutively in 5 stages including material calculation of evaporator; estimation of evaporator temperature mode; hydrodynamic and thermal predictions; estimation of heat transfer coefficient. The developed mathematical model was applied to stationary direct flow evaporation using Mathcad Prime software. In order to perform high quality analysis and to verify adequacy of the mathematical model, 12 criteria were selected characterizing evaporation efficiency in evaporator. Advantages of the developed mathematical model were highlighted and substantiated, practical recommendations on its application were given upon efficiency estimation of vacuum evaporation with mechanical recompression of water vapor.Â Â